HOW IS THE QUALITY OF READING TEST ITEMS ON ENGLISH SUBJECT? - Yulia Agustina; Nila Hayati; M. Adib Nazri (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2023)
The objective of the study is to ascertain the quality of the reading test items on English subject for the eighth students at SMPN 12 Tasikmalaya. Those items were analyzed based on difficulty level items, discrimination power, and distractor effectivity. This study employed descriptive quantitative. It is implemented to describe the quality of reading test item of eighth students of SMPN 12 Tasikmalaya. Whereas, quantitative data used as the data or information in the form of numerical data and analyzed it by using Item and Test Analysis (ITEMAN) program 3.0 version. The researchers had already conducted the study on reading in previous study, so in collecting the data, the researcher used the documentation. It used to know the quality of reading test items that had been made by the first researcher. The results showed that: 1) based on difficulty level of items indicated 14 (23%) items in easy, 32 (53%) items in medium, and 14 (23%) items in hard. Dealing to discrimination power of items, it showed that 51 (85%) items in very good, 5 (8%) in good, 0 (0%) in enough, and 4 (7%) in poor, must be discarded. Meanwhile, the distractor effectivity on reading test items on English subject of eighth students of SMPN 12 Tasikmalaya were: 44 (73%) items in function, 12 (420%) items in enough, 2 (7%) items in unfunctional, and 0 (0%) items in poor. Overall, the quality of reading test which had been made by the first researcher in previous study was in good quality.